Perceptions of Unqualified Statutory Audit Reports: The Case in Malta - Shannon Muscat; Konrad Farrugia; Peter J. Baldacchino; Norbert Tabone; Simon Grima (Sekolah Tinggi Ekonomi dan Bisnis Islam Lampung, 2021)
In this paper we lay out the results of a study on the perceptions of three Maltese stakeholder groups, namely external auditors, financial advisers and bank lending officers, pertaining to the communication and information aspects of the recently revised audit reporting standards. To do this we adopted a two phase sequential mixed-method approach using a questionnaire which was first distributed to the three stakeholder groups. Subsequently, the quantitative data collected in the first phase was analysed and discussed in semi-structured interviews conducted with a sample of twelve participants. Findings indicate that the most important section in the unqualified audit report is by far the auditor’s opinion. This is because it helps users determine the reliance that they can place on an entity’s accompanying financial statements when making financial decisions. However, users proved sceptical on the clarity of the unqualified audit report’s message and the technical jargon contained therein. This is primarily due to the users’ lack of understanding of the scope of the audit, its intended objectives and the technical jargon incorporated in the report.